التخاطب مع الأقران في تطوير مهارة الكلام باللغة العربية بوصفها لغة ثانية - Sabihah Abdul Kadir (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims at learning how effective peer interaction is in developing speaking skill in Arabic as a second language in classroom among Arabic majoring students and the extent of its practice among students in the classroom, as well as looking into how the practice was between male and female samples. The participants of this study are 35 students from the Department of Arabic Language and Literature at the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia. The researcher relies on the qualitative and quantitative approaches to obtain the results using in indirect observation within the classroom and participants' self-assessment survey. The research found that participants have different levels of peer interaction in the classroom, that the participants gain language from their peers and through constant interaction and practices within the classroom, their language proficiency developed. The results also indicated that males and females differ in the use of language during classroom discussions.